PENGARUH KECEPATAN DAN LAMA WAKTU SENTRIFUGASI DARAH TERHADAP JUMLAH TROMBOSIT PADA PROSES PEMBUATANPLATELET RICH FIBRIN - Andries Pascawinata; Andriansyah Andriansyah; Refo Bismanevi (Universitas Baiturrahmah, 2021)
Introduction: One of the most developed tissue engineering techniques to improve and spur the wound healing process in damage of soft and hard tissues of the oral cavity is the application of Platelet-Rich Fibrin (PRF). PRF contains many growth factors. Many studies have shown differences in the PRF preparation process especially in the variable speed and centrifugation time resulting in varied clinical trial results. Purpose: This study aims to find the effects of speed and time of centrifugation on the number of thrombocytes. Methods: In this experimental laboratory study, the samples were rat blood that was put into a vacuum tube centrifuged at different speeds and times. The sampling comprises 25 rat blood samples for the variable of the centrifugation speed and 25 rat blood samples for the centrifugation time, after which the number of histologically-formed thrombo-cytes was calculated. One-way ANOVA test was used for data analysis. Results: One-way ANOVA parametric test-assisted statistical analysis in the centrifugation speed group obtained a sig value of 0.000 <0.05, suggesting that the centrifugation speed was significantly affected the number of thrombocytes. One-way ANOVA test in the centrifugation time group obtained a sig value of 0.000 <0.05, indicating that all tested groups significantly affected the number of thrombocytes. Conclusion: Speed and time of blood centrifugation affect the number of thrombocytes in the process of Platelet-Rich Fibrin preparation